High-Quality and Enhanced-Resolution Single-Pixel Imaging Based on Spiral Line Array Laser Source - Guozhong Lei; Haolong Jia; Wenchang Lai; Wenhui Wang; Wenda Cui; Yan Wang; Hao Liu; Kai Han (IEEE Photonics Journal)
Single-pixel imaging (SPI) is a novel computational imaging technique which combines illumination light fields and single-pixel detection values to reconstruct the image. Therefore, the generation method of the illumination light fields affects the imaging efficiency and quality. We propose a spiral line array laser source which can generate random illumination light fields without periodicity in the normalized second-order correlation function g(2). It also has a lower full width at half maxima value (FWHM). In numerical simulations and experiments, the compressed sensing based on total variation algorithm is adopted to reconstruct the image. We demonstrate that the novel array is capable of obtaining images of superior quality and resolution compared to existing array laser sources, including hexagonal and Fermat spiral arrays. Combined with the fiber lasers and electro-optical phase modulators, it is expected to achieve high-speed modulation for light fields and high emitting power. Therefore, this method has significant potential for application in remote target detection and recognition.